Myxedema Coma with Cardiogenic Shock: Diagnostic Challenges and Risks of Amiodarone in Acute Thyroid Failure - Jean Carlos Ramos Cardona; Gunjan Mundhra; Munachiso Egbo; Veniamin Melnychuk; Suzanne Quinn Martinez (HCA Healthcare Journal of Medicine, 2026)
Background Myxedema coma is a rare but life-threatening manifestation of severe hypothyroidism characterized by altered mental status, hypothermia, bradycardia, and multiorgan dysfunction. Delayed diagnosis is common, particularly in elderly patients with multiple comorbidities. Cardiac complications, including malignant arrhythmias, are underrecognized contributors to morbidity and mortality. Profound hypothyroidism compromises cardiac myocyte function through reduced activity of enzymes involved in calcium uptake, leading to impaired myocardial contraction and relaxation. This results in decreased heart rate, reduced cardiac output, and altered left ventricular function, which may be further exacerbated in patients with heart failure with reduced ejection fraction. Prolongation of the ventricular action potential and QT interval is frequently observed, predisposing the patient to ventricular irritability and malignant arrhythmias, including acquired torsades de pointes. Case Presentation A 72-year-old woman with hypothyroidism, heart failure with reduced ejection fraction, chronic kidney disease, and a history of breast cancer presented to the emergency department with progressive weakness, dyspnea, edema, and confusion. Laboratory evaluation revealed the thyroid-stimulating hormone to be greater than 150 mIU/L and free thyroxine to be less than 0.3 ng/dL, which is consistent with severe hypothyroidism. A Popoveniuc diagnostic score of 95 was calculated, supporting a diagnosis of myxedema coma. The patient developed transient wide-complex tachycardia and was treated with intravenous (IV) amiodarone. She subsequently experienced worsening encephalopathy, hypotension, and bradyarrhythmia, which required intubation, multiple vasopressors, IV levothyroxine, hydrocortisone, fludrocortisone, and mechanical ventilation. Transthoracic echocardiography demonstrated a left ventricular ejection fraction of 12%. Her course progressed to cardiogenic shock necessitating biventricular mechanical circulatory support and continuous renal replacement therapy prior to transferring to a tertiary care center. Conclusion This case illustrates the complex interplay between severe hypothyroidism, advanced systolic heart failure, QT prolongation, and ventricular tachyarrhythmias in myxedema coma. Although amiodarone is commonly used for ventricular arrhythmia management due to its acute electrical stabilizing properties, its effects on thyroid hormone metabolism warrant caution in patients with underlying thyroid disease. Early recognition and coordinated endocrine cardiac management are critical to improving outcomes in this high-risk population.